Correlation between lower extremities symmetrical index and intensification of lower back pain in patients after hospital rehabilitation - Kołodziej, Krzysztof; Kwolek, Andrzej; Rusek, Wojciech; Przysada, Grzegorz; Szpunar, Paweł (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">On the faith of own research who was perform in 2003 year, investigators estimated symetrical loading index and intensification of lower back pain in patients after conservative treatment and surgical procedure then they was rehabilitated. To research include 79 patients ( 50 after conservative treatment and 29 after surgical research ). Autors stated correlations between symetrical loading index and intensificatio of low back pain. Lower extermities symetrical loading index can be objective measure to estimate progress of rehabilitation.